2022
DOI: 10.3390/su142013088
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Watershed Best Management Practices Spatial Optimal Layout under Uncertainty

Abstract: Watershed Best management Practices (BMPs) spatial optimal layout would be affected by uncertainty, and there are still three problems which are worthy of studying in the present studies of watershed BMPs spatial optimal layout under uncertainty: (1) how to integrate multiple uncertainties in optimization model effectively; (2) how to avoid subjective weight in multi-objective uncertainty model; (3) how to develop more elastic schemes for uncertainty impact. To solve the mentioned problems, this study takes Zh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…The alarming rate of TN and TP loading entering water bodies has posed critical challenges, notably the escalating issue of eutrophication in lakes, compromising the quality of drinking water and impacting various water-related activities [20][21][22]. In order to minimize the adverse effects of nutrient pollution in water bodies, many researchers in recent studies suggested that conservation methods, also known as Best Management Practices (BMPs), including vegetative filter strips (VFS), grass waterways (GWW), fertilizer reduction (FR), crop rotation (CR), and cover crop (CC) have been widely recommended as viable mitigation measures to reduce non-point pollution and improve water quality in impaired waterbodies [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The alarming rate of TN and TP loading entering water bodies has posed critical challenges, notably the escalating issue of eutrophication in lakes, compromising the quality of drinking water and impacting various water-related activities [20][21][22]. In order to minimize the adverse effects of nutrient pollution in water bodies, many researchers in recent studies suggested that conservation methods, also known as Best Management Practices (BMPs), including vegetative filter strips (VFS), grass waterways (GWW), fertilizer reduction (FR), crop rotation (CR), and cover crop (CC) have been widely recommended as viable mitigation measures to reduce non-point pollution and improve water quality in impaired waterbodies [23][24][25].…”
Section: Introductionmentioning
confidence: 99%